Aramaica Qumranica: Proceedings of the Conference on the Aramaic Texts from Qumran at Aix-en-Provence (June 30-July 2, 2008) - Berthelot, Katell; Stökl Ben Ezra, Daniel (Studies on the Texts of the Desert of Judah, 2010)
The articles in this book tackle important linguistic, exegetical and historical questions concerning the Aramaic scrolls from Qumran, addressing for instance the issue of their relevance to the development of apocalypticism and messianism in the Jewish tradition